2020
DOI: 10.1021/acsmaterialslett.0c00134
|View full text |Cite
|
Sign up to set email alerts
|

A Thioxanthenothioxanthene-based Hole Transporter with 2D Molecular Stacking for Efficient and Thermostable Perovskite Solar Cells

Abstract: Maintaining persistent thin-film morphology under certain thermal stress is desirable for durable operation of multi-layer organic optoelectronic devices. We herein report a thioxanthenothioxanthene-centered hole-transporter (N 3 ,N 3 ,N 9 ,N 9 -tetrakis(4-methoxyphenyl)thioxantheno[2,1,9,8klmna]thioxanthene-3,9-diamine, TXTX-OMeDPA) characteristic of two-dimensional molecular stacking in a single crystal. TXTX-OMeDPA can be solution-processed into smooth thin films with suitable energy level and good hole mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…42 Clearly, the close stacking interactions between the HTMs induced by the additional intermolecular S•••S interactions in the dithiolane-ring-based LYC-1 is responsible for a higher hole mobility than that of CT1. 46,47 The high hole mobility for LYC-1 is expected to promote the performance of PSCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…42 Clearly, the close stacking interactions between the HTMs induced by the additional intermolecular S•••S interactions in the dithiolane-ring-based LYC-1 is responsible for a higher hole mobility than that of CT1. 46,47 The high hole mobility for LYC-1 is expected to promote the performance of PSCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[ 17 ] When the temperature is close to T g , the relaxation kinetics will be greatly accelerated, for example, crystallization is prone to occur, resulting in a serious degradation of device performance. [ 18–21 ] Therefore, several methods have been explored to boost the T g of organic semiconductors. [ 22–32 ] Experimental studies have shown that some key structure factors such as molecular weight, main‐chain rigidity, side‐chain architecture, and intermolecular π⋅⋅⋅π interactions can tailor the T g of conjugated polymers, and thus the mechanical robustness.…”
Section: Introductionmentioning
confidence: 99%
“…For small molecular organic semiconductors, the achievement of thermostable PSCs can be generally ascribed to high T g s of some new materials. 15,19,21 Under thermal stress, the microscopic morphology of a HTL may gradually change. This may bring forth enlarged interfacial contact resistance and hole transport resistance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For low-cost, durable PSCs it is imperative to tailor an ideal HTL with combined properties of proper energy level, large conductivity, high glass transition temperature ( T g ), and good solution-processability. The past decade has witnessed an active exploration of various hole transport materials (HTMs) for PSCs, including inorganic semiconductors, polymeric semiconductors, and molecular semiconductors, some of which ,,,, have been demonstrated for over 21%-efficiency PSCs with certain durability at an elevated temperature. For small molecular organic semiconductors, the achievement of thermostable PSCs can be generally ascribed to high T g s of some new materials. ,, Under thermal stress, the microscopic morphology of a HTL may gradually change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation